Design and synthesis of novel pyrrolo[2,3-b]pyridine derivatives targeting (V600E)BRAF - Abdel-Maksoud, Mohammed S.; Ali, Eslam M. H.; Ammar, Usama M.; Mersal, Karim I.; Yoo, Kyung Ho; Oh, Chang-Hyun (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Several pyrrolo[2,3-b]pyridine-based B-RAF inhibitors are well known and some of them are currently FDA approved as anticancer agents. Based on the structure of these FDA approved B-V600E-RAF inhibitors, two series of pyrrolo[2,3-b]pyridine scaffold were designed and synthesized in attempt to develop new potent B-V600E-RAF inhibitors. The 38 synthesized compounds were biologically evaluated for their B-V600E-RAF inhibitory effect at single dose (10 mu M). Compounds with high percent inhibition were tested to determine their IC50 over (V600E)BRAF. Compounds 34e and 35 showed the highest inhibitory effect with IC50 values of 0.085 mu M and 0.080 mu M, respectively. Headed for excessive biological evaluation, the synthesized derivatives were tested over sixty diverse human cancer cell lines. Only compound 35 emerged as a potent cytotoxic agent against different panel of human cancer cell lines.
Keywords: BRAF MUTATIONS; SIGNALING PATHWAY; RAF KINASE; MULTIKINASE INHIBITOR; MAPK PATHWAY; MELANOMA; MUTANT; SENSITIVITY; ACTIVATION; SORAFENIB